Evaluation of the characteristics of plastic explosive adhered by liquid natural rubber - Doan, Khai Minh; Tuan, Nguyen Minh; Anh, Nguyen Tuan; Nhan, Pham Duc (Vietnam Journal of Science and Technology, 2020)
Plastic explosive (PBX) is an explosive that a polymer binder is used to reduce the sensitivity of high explosives for various applications. This paper presents the characteristics of the PBXs based on liquid natural rubber (LNR) and hexogen (RDX). The PBXs are prepared according to a modified formulation of the Composition C-4. The plasticity of the PBXs is determined according to the MIL-STD-650 method 211.1. The uniaxial compression of the PBXs examined by the STANAG 4443. The test of the sensitivity of PBXs to friction is carried out by STANAG 4487. The thermal stability is tested by the STANAG 4556 at 100 oC for 40 hours. The results indicated that the plasticity is found to be more than 0.018 in accordance with the MIL-C-45010A. Further, the modulus of elasticity, yield strength, and strain can be adjusted by the composition of the LNR binder. In addition, the frictional sensitivity of the PBXs is significantly reduced to more 360 N of the load. The thermal stability is in the range of 0.156 to 0.225 ml.g-1 and completely meets technical requirements. Therefore, the direction of using LNR as a binder for PBXs gives acceptable results for further researches.